Preventing newborn deaths due to prematurity. (October 2016) - Azad, Kishwar; Mathews, Jiji
Abstract : Preterm births (PTBs), defined as births before 37 weeks of gestation account for the majority of deaths in the newborn period. Prediction and prevention of PTB is challenging. A history of preterm labour or second trimester losses and accurate measurement of cervical length help to identify women who would benefit from progesterone and cerclage. Fibronectin estimation in the cervicovaginal secretions of a symptomatic woman with an undilated cervix can predict PTB within 10 days of testing. Antibiotics should be given to women with preterm prelabour rupture of membranes but tocolysis has a limited role in the management of preterm labour. Antenatal corticosteroids to prevent complications in the neonate should be given only when gestational age assessment is accurate PTB is considered imminent, maternal infection and the preterm newborn can receive adequate care. Magnesium sulphate for fetal neuroprotection should be given when delivery is imminent. After birth, most babies respond to simple interventions essential newborn care, basic care for feeding support, infections and breathing difficulties. Newborns weighing 2000 g or less, benefit from KMC. Babies, who are clinically unstable or cannot be given KMC may be nursed in an incubator or under a radiant warmer. Treatment modalities include oxygen therapy, CPAP, surfactant and assisted ventilation. Highlights: Preterm births are a major cause of neonatal mortality. Predictors include cervical length and cervicovaginal fibronectin levels. Kangaroo Mother Care (KMC) provides skin-to-skin contact between mother and baby, promotes bonding and breastfeeding. KMC is low cost, feasible and is suitable for stable infants, weighing <2500 g.